Gut microbiota composition in chemotherapy and targeted therapy of patients with metastatic colorectal cancer - Chen, Yen-Cheng; Chuang, Chia-Hsien; Miao, Zhi-Feng; Yip, Kwan-Ling; Liu, Chung-Jung; Li, Ling-Hui; Wu, Deng-Chyang; Cheng, Tian−Lu; Lin, Chung-Yen; Wang, Jaw-Yuan (Frontiers in Oncology, 2022)
Studies have reported the effects of the gut microbiota on colorectal cancer (CRC) chemotherapy, but few studies have investigated the association between gut microbiota and targeted therapy. This study investigated the role of the gut microbiota in the treatment outcomes of patients with metastatic CRC (mCRC). We enrolled 110 patients with mCRC and treated them with standard cancer therapy. Stool samples were collected before administering a combination of chemotherapy and targeted therapy. Patients who had a progressive disease (PD) or partial response (PR) for at least 12 cycles of therapy were included in the study. We further divided these patients into anti-epidermal growth factor receptor (cetuximab) and anti-vascular endothelial growth factor (bevacizumab) subgroups. The gut microbiota of the PR group and bevacizumab-PR subgroup exhibited significantly higher α-diversity. The β-diversity of bacterial species significantly differed between the bevacizumab-PR and bevacizumab-PD groups (P = 0.029). Klebsiella quasipneumoniae exhibited the greatest fold change in abundance in the PD group than in the PR group. Lactobacillus and Bifidobacterium species exhibited higher abundance in the PD group. The abundance of Fusobacterium nucleatum was approximately 32 times higher in the PD group than in the PR group. A higher gut microbiota diversity was associated with more favorable treatment outcomes in the patients with mCRC. Bacterial species analysis of stool samples yielded heterogenous results. K. quasipneumoniae exhibited the greatest fold change in abundance among all bacterial species in the PD group. This result warrants further investigation especially in a Taiwanese population.